2020
DOI: 10.2478/hukin-2020-0007
|View full text |Cite
|
Sign up to set email alerts
|

Mini-Basketball Training Program Improves Physical Fitness and Social Communication in Preschool Children with Autism Spectrum Disorders

Abstract: This investigation examined the effects of a 12-week mini-basketball training program (MBTP) on physical fitness and social communication in preschool children with autism spectrum disorders (ASD). The study applied a quasi-experimental design. Fifty-nine preschool children aged 3-6 years with ASD were assigned to either a MBTP group (n = 30) or a control group (n = 29). Participants in the MBTP group received a scheduled mini-basketball training program (5 sessions per week, forty minutes per session) for twe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
48
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 43 publications
0
48
0
1
Order By: Relevance
“…The mini-basketball training program (MBTP) conducted by two certified physical educators was adopted from previous studies [24][25][26][27] and operational details can be found in our published articles [13,28]. A program with various levels of difficulty was designed (Table 1), and a collective teaching mode was used to facilitate social interaction and communication among participants while parent's participation in and attendance at exercise sessions was strongly encouraged.…”
Section: Usual Care and Mini-basketball Training Programmentioning
confidence: 99%
See 2 more Smart Citations
“…The mini-basketball training program (MBTP) conducted by two certified physical educators was adopted from previous studies [24][25][26][27] and operational details can be found in our published articles [13,28]. A program with various levels of difficulty was designed (Table 1), and a collective teaching mode was used to facilitate social interaction and communication among participants while parent's participation in and attendance at exercise sessions was strongly encouraged.…”
Section: Usual Care and Mini-basketball Training Programmentioning
confidence: 99%
“…Up to now, various evidence-based ASD interventions (applied behavior analysis [8], discrete trial training [9], and pivotal response training [10]) that aimed to improve SC have been applied successfully, but to maximize such positive treatment effects, researchers have also started to encourage the use of physical exercise training programs as an adjuvant therapy for ASD children within usual care treatments [11][12][13]. Specifically, researchers found positive effects on antisocial behaviors [12] and SC-related outcomes (e.g., emotion regulation, social awareness, social cognition, social communication, and mannerisms) among ASD patients aged 3 to 12 years [11] following different physical training programs (e.g., swimming, jogging, martial arts, and basketball [14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, mini-basketball has the inherent characteristics of basketball and is designed for children under 12 years old, which is parallel with the physical and mental developmental characteristics of children. Mounting evidence has demonstrated that a mini-basketball training program (MBTP) can effectively improve the core symptoms of children with ASD, as well as promote the development of physical fitness [ 14 ], cognitive function [ 15 , 16 ], and other aspects. Therefore, mini-basketball has been regarded as a promising and valuable means of intervention; however, the neural mechanism by which an MBTP improves SC impairment remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Wang,JG Cai, KL Liu, ZM et al (2020). Effects of Mini-Basketball Training Program on Executive Functions and Core Symptoms among Preschool Children with Autism Spectrum Disorders.…”
mentioning
confidence: 99%